High-order vortex harmonics generation by bi-circular Laguerre-Gaussian laser fields with relativistic plasmas - Xie, Duan; Yin, Yan; Yu, Tongpu; Zhang, Hao; Zhou, Hongyu (Frontiers in Physics, 2022)
Vortex beams with ultra-high brilliance can greatly enrich the light and matter interaction process and even shed light on the unexpected information in relativistic nonlinear optics. Thus, we propose a scheme for relativistic intense vortex harmonic radiation by use of bi-circular Laguerre–Gaussian lasers irradiating relativistic plasmas. Three-dimensional particle-in-cell simulation results show that the emitted harmonics own controllable spin and orbital angular momentum simultaneously, which can be attributed to the vortex mirror model and the related conservation laws. Meanwhile, the conversion efficiency of harmonic generation can be tuned through adjusting the intensity ratio of the two driving field components.